Menjadi Gereja yang Inklusif dalam Konteks Keberagaman berdasarkan Injil Matius 8:5-13 - Mefibosed Radjah Pono (JURNAL TEOLOGI GRACIA DEO, 2022)
Exclusivity in religious groups, including Christianity, is a threat to a harmonious and peaceful life in the context of a pluralistic Indonesia. The church needs to be inclusive and reinterpret its presence in this context by learning from Jesus in his encounters with “others” as in the Gospel of Matthew 8:5-13. This study seeks to find the meaning of Jesus' attitude towards foreign officers and the healing that Jesus gave to officers' servants in the context of the Matthew congregation, as well as the kerygma for efforts to become an inclusive church in a pluralistic context in Indonesia. This study uses an interpretive description method with socio-historical interpretation. The result is that Matthew's Gospel demonstrates Jesus' inclusive attitude by accepting all people, not just Jews, to experience His love and salvation. The acceptance was not based on Jewish background, but because of faith in Jesus. Therefore, groups in Matthew's congregation must avoid exclusivity, mutual acceptance, and respect. The message for the church in Indonesia is that the church must stay away from exclusivity, Christianization efforts, but seek to reveal God's reign in the world. The church must be an inclusive church, loving and serving “others”, hearing and knowing “others” in order to see God's work in them. The presence of the church is seen through its service to all people, especially to solve humanitarian problems. Through her ministry, the church shows Christ to “others” so that they experience His saving works and believe in Him. AbstrakPaham dan sikap eksklusif dalam kelompok agama, termasuk agama Kristen merupakan ancaman bagi hidup yang rukun dan damai di konteks Indonesia yang plural. Gereja perlu bersikap inklusif dan memaknai kembali kehadirannya dalam konteks seperti ini dengan belajar dari Yesus dalam perjumpaannya dengan “yang lain” seperti dalam Injil Matius 8:5-13. Penelitian ini berupaya untuk menemukan makna sikap Yesus terhadap perwira asing dan penyembuhan yang diberikan Yesus kepada hamba perwira dalam konteks jemaat Matius, serta kerygma bagi upaya menjadi gereja yang inklusif dalam konteks plural di Indonesia. Penelitian ini menggunakan metode deskripsi interpretatif dengan tafsir sosio historis. Hasilnya adalah, Injil Matius memper-lihatkan sikap Yesus yang inkusif dengan menerima semua orang, bukan hanya orang Yahudi saja, untuk mengalami kasih dan keselamatan dari-Nya. Penerimaan itu bukan berdasarkan latar belakang Yahudi, tetapi karena iman kepada Yesus. Oleh karena itu, kelompok dalam jemaat Matius harus menjauhi sikap ekslusif, saling menerima dan menghormati. Pesannya bagi gereja di Indonesia adalah gereja harus menjauhi paham dan sikap eksklusif, upaya kristenisasi tetapi berupaya menyatakan pemerintahan Allah dalam dunia. Gereja harus menjadi gereja yang inklusif, mengasihi dan melayani “yang lain”, mendengar dan mengenal “yang lain”agar dapat melihat karya Allah dalam diri mereka. Kehadiran gereja terlihat melalui pelayanannya bagi semua orang, terutama untuk menyelesaikan masalah kemanusiaan. Melalui pelayanannya gereja memperlihatkan Kristus kepada “yang lain” sehingga mereka mengalami perbuatan penyela-matan-Nya dan percaya kepada-Nya.